PENGARUHCAREER DEVELOPMENT DAN WORK-LIFE BALANCE DIMEDIASI OLEH EMPLOYEEENGAGEMENT TERHADAP TURNOVER INTENTION - Ni Nyoman Dwi Ari Candra Ningsih; Ni Made Yudhaningsih; I Made Anom Arya Pering (Politeknik Ubaya, 2022)
Abstract Human Resources (HR) is the main element of the organization. Developing yourself and providing a balanced work life can minimize the rate of employee turnover or termination (turnover intention). This study has the urgency of the turnover rate at PT. Bank Rakyat Indonesia (Persero) Tbk. Denpasar Gajah Mada Branch Office which will increase by 7 people in 2021 and its relationship with career development and work life balance. The researcher aims to determine the effect of career development and work-life balance mediated by employee engagement on turnover intention. Hypothesis Testing using Hypothesis Testing (F-test) in the ANOVA Model and Hypothesis Testing (T-test) in the Coefficients Model with quantitative data with a sample of 80 people from a population of 393 based on the Slovin Model with the instrument in the form of a questionnaire. The results obtained are F_calculated career development, work life balance and employee engagement 1,203 and Sig. 0.315 > 0.050, it can be stated that career development has